Heart Rate Variability Indexes in Dementia: A Systematic Review with a Quantitative Analysis - da Silva, Vanessa P.; Ramalho Oliveira, Bruno Ribeiro; Tavares Mello, Roger Gomes; Moraes, Helena; Deslandes, Andrea Camaz; Laks, Jerson (Current Alzheimer Research, 2018)
Background: Decreased heart rate variability (HRV) indexes indicate low vagal activity and may be associated with development of dementia. The neurodegenerative process is associated with the cardiovascular autonomic control. Objective: The aim of this systematic review was to investigate the effect size (ES) magnitude of the HRV indexes in the evaluation of autonomic dysfunction in older persons with dementia. Methods: PubMed (Medline), Web of Science, Scopus, Scielo, Lilacs, and APA Psycnet were consulted. Complete original articles published in English or Portuguese, investigating the association between autonomic dysfunction and dementia, using the HRV indexes were included. Results: The search identified 97 potentially relevant articles. After screening the full text, eight articles were included in the qualitative analysis and six were included in the quantitative analysis. Almost all indexes showed a negative ES for all types of dementia and mild cognitive impairment. The most common frequency band of the power spectrum density function was the high frequency, which was reported by six studies. The meta-analysis of high frequency power in Alzheimer's disease group showed high heterogeneity and inconsistent results. Conclusion: The negative effect size suggests an autonomic dysfunction in all types of dementia as well as mild cognitive impairment. However, further analysis is necessary to support these results.
Keywords: Autonomic nervous system